Determinants of peer education on sexual and reproductive health and rights among in-school adolescents in Ebonyi State, Nigeria - Chinyere O. Mbachu; Ifunanya C. Agu; Irene I. Eze; Obinna E. Onwujekwe (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Peer education has contributed to increased knowledge and preventive behaviors of adolescents toward reproductive health matters with the unique feature of maintaining peer-to-peer learning ability and sustaining intervention gains. This study examined the factors that predict the agency of in-school adolescents as peer educators on the sexual and reproductive health and rights (SRHR) of adolescents. MATERIALS AND METHODS: A cross-sectional study was conducted on 257 adolescent boys and girls, purposively selected from six public secondary schools that had received a package of interventions that aimed to improve peer-to-peer education on SRHR in Ebonyi State, Nigeria. Data were collected using a pretested structured interviewer-administered questionnaire. Univariate and multivariate analyses were performed. The level of statistical significance was determined at a P value < 0.05 and a 95% confidence limit. RESULTS: Almost all the students (98.05%) believed that adolescents need information on SRHR, which should be provided in the schools; however, 66.93% had ever shared information with their peers on the SRHR. The predictors of the practice of peer education on SRHR include being in senior secondary (adjusted odds ratios (AOR) =2.889, P = 0.026), participation in SRHR campaigns (AOR = 6.139, P = 0.005), receiving information, education and communication materials (AOR = 0.266, P = 0.042), and discussing SRH matter with adult family members (AOR = 2.567, P = 0.026). CONCLUSION: The practice of peer education among adolescents was determined by their level in school, availability of support structures such as parent-child communication, and program-related factors. Therefore, public health initiatives should prioritize these factors to strengthen adolescents' agency as peer educators on the SRHR of young people.